Desimination of innovation in the digitalization of Padukuhan Gading tourism village - Iswanto Suwarno; Yoga Ihsan Rianto; Ramadhani Prayoga; Nia Maharani Raharja; Robbi Rahim; Ada Adoley Allotey; Mary Puthern; Lela Khartishvili (Peneliti Teknologi Teknik Indonesia, 2023)
Padukuhan Gadingan has quite a lot of tourism potential but there are still many people who don't know about this tour. With these problems, the UMY KKN team carried out community service by implementing a digital tourism village to promote the village. In our community service project, we socialize Kumparan and create social media accounts for Karang Taruna, the names of the social media accounts are Instagram and Kumparan, with social media accounts it can help to disseminate art and tourism activities in Padukuhan Gadingan so that it can developing and enlivening tourism and activities at Padukuhan Gadingan with digitalization innovations is an effective renewal strategy in promoting various information or potential that exists in each region.